An Interesting Case of Bilateral Hilar Lymphadenopathy Presented with Visual Impairment - MT, Chandramouli; Baikunje, Nandakishore; Y., Sunil Kumar; K., Subrahmanya Bhat; Bajaj, Darshan; Hosmane, Giridhar Belur (Journal of Health and Allied Sciences NU, 2021)
Sarcoidosis is a systemic granulomatous disease of unknown etiology. It primarily affects the lungs and lymphatics; however, the presentation is not always pulmonary. Uveitis is the presenting symptom in 5% of patients, predominantly in females. Cystoid macular edema is the most important sight-threatening sequela of ocular sarcoidosis. Histopathological evidence of noncaseating epithelioid granulomas from a biopsy is the gold standard for the diagnosis of ocular sarcoidosis. Diagnosis of sarcoidosis is made by exclusion of other causes of granulomatous disease, mainly tuberculosis and fungal infection and documentation of involvement of at least one additional organ system. The authors present a case of a patient with sarcoidosis involving lungs and eyes, who had uveitis as an initial presentation.
Keywords: EBUS TBNA; granulomatous lesion; sarcoidosis; uveitis